COMPARATIVE CHARACTERISTICS OF THORACOSCOPIC SURGERY FOR SPONTANEOUS PNEUMOTHORAX - Y. V. Chikinev; Y. A. Drobyazgin; A. Y. Litvintsev; K. I. Shcherbina (Сибирский научный медицинский журнал, 2019)
Comparative analysis of thoracoscopic methods of surgical treatment of spontaneous pneumothorax with bullous emphysema was performed. The material has been collected during the retrospective study of the medical documentation of the Department of Thoracic Surgery of the Novosibirsk State Regional Clinical Hospital of Ministry of Health of the RF. During the seven-year period from 2010 to 2017, 125 medical cases with different diagnoses were selected such as: spontaneous pneumothorax; bullous emphysema; recurrent spontaneous pneumothorax. The analysis of the entry criteria were specific pathological picture of chest organs multispiral computed tomography. The withdrawal criteria were conversion associated with technical complexity due to evident adhesive process (12 cases). The vast majority of complications were observed in patients underwent thoracoscopic lung resection. The manual intracorporal suture overlap on the lung tissue leads to a greater risk of prolonged air leakage in the postoperative period. Bullous diathermocoagulation has a small risk of prolonged air leakage in the postoperative period. The study findings require the development of an algorithm for spontaneous pneumothorax case management to reduce possible complications.